Sex pheromone and period gene characterization of Lutzomyia longipalpis sensu lato (Lutz & Neiva) (Diptera: Psychodidae) from Posadas, Argentina - Salomón, Oscar Daniel (2010)
Fil: Salomón, Oscar D.ANLIS Dr.C.G.Malbrán. Centro Nacional de Diagnóstico e Investigación de Endemo-Epidemias; Argentina.